Potential role for vascular surgeons during a COVID-19 outbreak: management, workload, and outcomes from the initiation of a central venous line service for patients with COVID-19 undergoing ventilation during the initial UK peak. Issue 3 (17th January 2021) - Liu, P; Lui, D; Cheema, S Mahmood; Hussain, S Tahir; Husain, T; Malina, M
Abstract : This is a report by a vascular unit in London on the initiation of a central venous line service for patients with COVID-19 undergoing ventilation during the initial UK peak. It includes views on management, workload, and overall outcomes.